Land Management and Sustainable Tourism. Case Recuay Province-Ancash - Cruz Reyes, Fray Masias (2010)
This research because the dimension of the subject is focused to recognize and evaluate the potential of tourism, its implication on the economy and quality of life of the people and this land was used as an instrument of territorial planning to make proper use and their sustainable. The province's tourism infrastructure is scarce and precarious, despite having tangible and intangible tourism resources, whose start value would increase employment and incomes. Water potential, likely making this province to invest in productive activities. The implementation of a Land Use Plan at the provincial level of the population consult proposals regarding the capabilities and limitations of land and the sustainable use of natural resources, seeking the reduction of imbalances in the territory and ensuring the investments.